High-Tg single-component epoxy adhesive for locking motor coil and preparation method of high-Tg single-component epoxy adhesive
By developing high-Tg single-component epoxy adhesives, using high-toughness epoxy resins and multifunctional epoxy resins and other raw materials, the problem of insufficient durability of existing insulating materials is solved, and efficient insulation for motor coil locking is achieved and extended The service life of the motor and simplifies the production process.
Patent Information
- Application Number
- CN202411175056.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2024-12-13
AI Technical Summary
The Tg value of existing insulating materials is low, which cannot meet the durability of the materials under extreme overheating conditions, resulting in a shorter service life and reduced reliability of the motor. In addition, the use of products on the market such as two-component epoxy adhesives is complicated or requires specific equipment, which is limited. Industrial application.
Develop a high Tg single-component epoxy adhesive. By synthesizing high toughness epoxy resins and combining multifunctional epoxy resins, low viscosity epoxy resins, isocyanate silanes and other raw materials, an adhesive with high Tg and toughness is prepared. , a simplified preparation method is adopted to meet the needs of motor coil locking.
The adhesive maintains excellent performance and adhesive strength at high temperatures, meets the temperature resistance requirements of motor winding insulation materials, extends the service life of the motor and improves reliability, and is simple to prepare and suitable for industrial production.
Smart Images

Figure CN119119930A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of adhesives, and in particular to a high-Tg single-component epoxy adhesive for locking motor coils and a preparation method thereof. Background Art
[0002] The motor is mainly composed of a motor stator, an electronic rotor and other accessories. The electronic stator and rotor contain windings made of copper wire. During the operation of the motor, the winding is vibrated and displaced, causing the motor to malfunction. Therefore, insulating and heat-resistant materials are required to fix the winding. During the operation of the motor under load, there is power loss in the motor, which will eventually turn into heat energy, causing the internal temperature of the motor to rise. The existing insulating materials have a low Tg and cannot meet the rapid aging of materials under extreme overheating conditions, shortening their service life and reducing the overall reliability of the motor.
[0003] In order to achieve high Tg effects, products on the market usually use two-component epoxies composed of multifunctional epoxy resins and phenolic resins, amines, acid anhydrides, etc.; or single-component epoxies composed of photoinitiators and thermal cations.
[0004] Patent CN115029089B uses iodonium salt cation curing, which is a photo-initiated adhesive. It requires customers to equip specific wavelength equipment, and the curing depth is limited, which is not conducive to large-scale industrialization.
[0005] Patent CN104559064A is a multi-component adhesive. When using, it needs to be accurately weighed according to the ratio and mixed evenly before use. Inaccurate weighing and uneven mixing are prone to cause poor product consistency.
[0006] To this end, the present application provides a high Tg single-component epoxy adhesive for locking motor coils and a preparation method thereof. Summary of the invention
[0007] The present application provides a high Tg one-component epoxy adhesive for locking motor coils and a preparation method thereof, by synthesizing an epoxy resin with high Tg and toughness, and using the epoxy resin to make a high Tg one-component epoxy adhesive for locking motor winding coils, so as to overcome the problem of insufficient service life of existing products on the market.
[0008] The technical solution adopted by this application to solve its technical problem is:
[0009] In a first aspect, the present application provides a high Tg one-component epoxy adhesive for locking a motor coil, comprising the following raw materials in parts by weight:
[0010] 5-25 parts of multifunctional epoxy resin, 15-50 parts of high-toughness epoxy resin, 0.1-0.5 parts of thixotropic agent, 0.5-1.5 parts of colorant, 0.1-0.5 parts of wetting and dispersing agent, 0.5-2 parts of defoaming agent, 15-40 parts of functional filler, 0.5-3 parts of antioxidant, 5-12 parts of curing agent;
[0011] The high toughness epoxy resin comprises the following raw materials by weight percentage:
[0012] Low viscosity epoxy resin 67.5~90%
[0013] Isocyanate silane 9.4~30%
[0014] Catalyst 0.1~0.5%
[0015] Water reducing agent 0.5-2%;
[0016] At least one of the low-viscosity bisphenol A epoxy resin and the low-viscosity bisphenol F epoxy resin;
[0017] The isocyanate silane is at least one of 3-isocyanate propyl trimethoxy silane and 3-isocyanate propyl triethoxy silane.
[0018] Preferably, the catalyst is at least one of dibutyltin dilaurate, bismuth isooctanoate, and bismuth neodecanoate.
[0019] Preferably, the water reducing agent is a molecular sieve.
[0020] Preferably, the method for preparing the high-toughness epoxy resin comprises the following steps:
[0021] The material is taken according to the weight percentage of the raw material of the high-toughness epoxy resin; the low-viscosity epoxy resin, the catalyst and the water reducer are mixed and vacuumized; the temperature is lowered, and isocyanate silane is added to react; after the reaction is completed, the high-toughness epoxy resin is washed and dried to obtain the high-toughness epoxy resin.
[0022] The multifunctional epoxy resin is at least one of 4,4'-diaminodiphenylmethane epoxy resin, 4-(diglycidylamino)phenyl glycidyl ether, sorbitol glycidyl ether, and phenol-type novolac epoxy resin.
[0023] Preferably, the thixotropic agent is at least one of bentonite, fumed silica and polyethylene wax.
[0024] Preferably, the colorant is at least one of carbon black and titanium dioxide.
[0025] Preferably, the wetting and dispersing agent is at least one of a polyphosphate solution, an acidic polyester solution, an unsaturated polyamine amide and a salt solution of an acidic polyester.
[0026] Preferably, the defoaming agent is at least one of a foam-breaking polymer, polysiloxane, and polyether-modified polysiloxane.
[0027] Preferably, the functional filler is at least one of nano-silicon dioxide, nano-aluminum oxide, and silicon dendrimer.
[0028] Preferably, the antioxidant is at least one of a hindered amine antioxidant, a phosphite antioxidant, and a hindered phenol antioxidant.
[0029] Preferably, the curing agent is at least one of microencapsulated dicyandiamide, boron amine complexes of borate esters, microencapsulated hydrazides, and modified imidazole adducts.
[0030] In a second aspect, a method for preparing the above-mentioned high Tg one-component epoxy adhesive for locking a motor coil is provided, comprising the following steps:
[0031] Take materials according to the weight of the raw materials of the high Tg single-component epoxy adhesive for locking the motor coil; put multifunctional epoxy resin, high-toughness epoxy resin, thixotropic agent, colorant, wetting dispersant, defoamer, functional filler and antioxidant into a reaction container, mix them evenly, and then heat to 100° C. for vacuum treatment;
[0032] The temperature is lowered to 40-60° C., a curing agent is added, and the mixture is mixed evenly under vacuum conditions to obtain a high Tg single-component epoxy adhesive for locking the motor coil.
[0033] The beneficial effects of this application are:
[0034] 1. The high Tg one-component epoxy adhesive for locking the motor coil described in the present application is prepared by preparing a high-toughness epoxy resin, and then preparing a high Tg one-component epoxy adhesive for locking the motor winding coil. The epoxy adhesive has a high Tg and a certain toughness. After the epoxy adhesive is fully cured and aging tested, the performance and adhesion of the colloid itself are still relatively excellent, which meets the requirements of the insulation material for locking the motor winding coil for temperature resistance and service life, thereby ensuring the overall reliability and service life of the motor and reducing the failure rate in use.
[0035] 2. The high Tg single-component epoxy adhesive for locking the motor coil described in this application has a Tg value that is higher than the 130°C requirement for Class B materials, the hottest temperature in the winding insulation when the motor is running, indicating that the epoxy adhesive fully meets the requirements as an insulating material; at the same time, from the analysis of the elastic modulus, the modulus at 25°C is only 6951 MPa, indicating that the epoxy adhesive has a certain toughness, thereby ensuring that it will not fall off during the operation of the motor and ensuring the service life of the product.
[0036] 3. The high Tg single-component epoxy adhesive for locking the motor coil described in this application has no attenuation in the bulk strength and shear strength data after aging, and even has a certain improvement, which can fully solve the problem of insufficient life faced by current conventional epoxy adhesives. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0038] Figure 1 is the Tg value of the epoxy adhesive of Example 1 described in this application;
[0039] Figure 2 is the Tg value of the epoxy adhesive of Comparative Example 1 described in this application;
[0040] Figure 3 This is a graph of the elastic modulus of the epoxy adhesive of Example 1 described in this application;
[0041] Figure 4 This is a graph of the elastic modulus of the epoxy adhesive of Comparative Example 1 described in this application;
[0042] Figure 5 It is the body strength variation diagram of Example 1 and Comparative Example 1;
[0043] Figure 6 This is a graph showing the shear strength variation of Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0044] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.
[0045] As used herein, "and / or" includes the term of any and all combinations of one or more associated listed items. The terms used herein are only used to describe specific embodiments and are not intended to limit the present invention. As used herein, the singular forms "a", "an", "an" and "the" are also intended to include the plural forms, unless the context clearly indicates otherwise. It is further understood that "including", when used in this specification, specifies the stated features, integers, steps, operations, elements and / or compositions, but does not exclude the existence or addition of one or more other features, integers, steps, operations, elements, compositions and / or combinations thereof.
[0046] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the invention belongs. It is further understood that terms, such as defined in commonly used dictionaries, are interpreted in accordance with their meanings in the context of the relevant art and are not in an idealized or overly formal sense unless explicitly so defined herein.
[0047] The exemplary invention described herein may appropriately lack any one or more element limitations that are not specifically disclosed herein. Therefore, the terms "comprise", "include", "contain", etc. should be understood broadly and non-restrictively. In addition, the terminology used herein is used as a description, not a limitation, and it is unintentional to use these terminology expressions that do not include any equivalent characteristics, but only describe some of their characteristics, but various modifications are possible within the scope of the present invention according to the rights. Therefore, although the present invention has been specifically disclosed by preferred embodiments and optional features, the modifications disclosed herein to embody the changes of the present invention may be recorded by those skilled in the art, and such modifications and changes will be considered to be within the scope of the present invention.
[0048] A high Tg one-component epoxy adhesive for locking motor coils, measured in weight percentage and in parts by weight, comprises the following raw materials:
[0049] 5-25 parts of multifunctional epoxy resin, 15-50 parts of high-toughness epoxy resin, 0.1-0.5 parts of thixotropic agent, 0.5-1.5 parts of colorant, 0.1-0.5 parts of wetting and dispersing agent, 0.5-2 parts of defoaming agent, 15-40 parts of functional filler, 0.5-3 parts of antioxidant, 5-12 parts of curing agent;
[0050] Specifically, the multifunctional epoxy resin is at least one of 4,4'-diaminodiphenylmethane epoxy resin, 4-(diglycidylamino)phenyl glycidyl ether, sorbitol glycidyl ether, and phenol-type novolac epoxy resin. The weight of the multifunctional epoxy resin is 5 to 25 parts, and can be any value of 5 parts, 8 parts, 18 parts, and 25 parts, as long as it meets the range requirement of 5 to 25 parts (including the endpoint values of 5 parts and 25 parts). In the present application, the multifunctional epoxy resin plays a role in increasing the crosslinking density, improving heat resistance and mechanical strength in the adhesive. Because its molecules contain multiple reactive functional groups, it can form a tighter crosslinking network with other resin molecules, thereby improving the overall performance of the adhesive.
[0051] Specifically, the thixotropic agent is at least one of bentonite, fumed silica, and polyethylene wax. The weight portion of the thixotropic agent is 0.1 to 0.5 parts, and can specifically be any value of 0.1, 0.2, 0.3, and 0.5 parts, as long as it meets the range requirement of 0.1 to 0.5 parts (including the endpoint values of 0.1 and 0.5). In the present application, the thixotropic agent can adjust the rheological properties of the adhesive, so that it has a higher viscosity when stationary to prevent flowing, and the viscosity is reduced when subjected to shear force (such as stirring or coating), which is convenient for processing and coating. The thixotropic agent helps to improve the construction performance and coating uniformity of the adhesive.
[0052] Specifically, the colorant is at least one of carbon black and titanium dioxide. The weight of the colorant is 0.5 to 1.5 parts, and can be any value of 0.5, 0.8, 1.2, and 1.5 parts, as long as it meets the range requirement of 0.5 to 1.5 parts (including the endpoint values of 0.5 and 1.5). In this application, the colorant is mainly used to adjust the color of the adhesive to meet different appearance requirements or marking requirements. In the locking of motor coils, appropriate color marking helps to distinguish different parts or perform quality control.
[0053] Specifically, the wetting and dispersing agent is at least one of a polyphosphate solution, an acidic polyester solution, an unsaturated polyamine amide and a salt solution of an acidic polyester. The weight of the wetting and dispersing agent is 0.1 to 0.5 parts, and can be any value of 0.1 parts, 0.2 parts, 0.3 parts, and 0.5 parts, as long as it meets the range requirement of 0.1 to 0.5 parts (including the endpoint values of 0.1 parts and 0.5 parts). In the present application, the wetting and dispersing agent can improve the wettability and permeability of the adhesive to the surface of the motor coil, so that the adhesive can better adhere to the coil surface and be evenly distributed. This helps to improve the adhesion and locking effect of the adhesive.
[0054] Specifically, the defoamer is at least one of a foam-breaking polymer, a polysiloxane, and a polyether-modified polysiloxane. The weight portion of the defoamer is 0.5 to 2 parts, and can be any value among 0.5 parts, 0.8 parts, 1.2 parts, 1.5 parts, and 2 parts, as long as it meets the range requirement of 0.5 to 2 parts (including the endpoint values of 0.5 parts and 2 parts). In the present application, bubbles may be generated during the preparation and coating of the adhesive due to stirring or air mixing. The defoamer can destroy the surface tension of the bubbles, causing the bubbles to burst quickly and release gas, thereby avoiding the influence of the bubbles on the performance of the adhesive.
[0055] Specifically, the functional filler is at least one of nano-silicon dioxide, nano-alumina, and silicon dendritic polymer. The weight of the functional filler is 15 to 40 parts, and can be any value of 15 parts, 18 parts, 28 parts, 35 parts, and 40 parts, as long as it meets the range requirement of 15 to 40 parts (including the endpoint values of 15 parts and 40 parts). In this application, functional fillers (such as inorganic fillers, reinforcing fibers, etc.) can enhance the mechanical properties, heat resistance, chemical resistance, etc. of the adhesive. They form a physical barrier or provide additional support points by filling in the resin matrix, thereby improving the overall performance of the adhesive.
[0056] Specifically, the antioxidant is at least one of a hindered amine antioxidant, a phosphite antioxidant, and a hindered phenol antioxidant. The weight portion of the antioxidant is 0.5 to 3 parts, and can be any value among 0.5 parts, 0.8 parts, 1.2 parts, 1.5 parts, 2 parts, and 3 parts, as long as it meets the range requirement of 0.5 to 3 parts (including the endpoint values of 0.5 parts and 3 parts). In the present application, the antioxidant can delay the aging process of the adhesive and prevent its performance degradation due to long-term use or exposure to harsh environments such as high temperature and ultraviolet rays. The antioxidant protects the molecular structure of the adhesive from being destroyed by mechanisms such as capturing free radicals and blocking oxidation reactions.
[0057] Specifically, the curing agent is at least one of microencapsulated dicyandiamide, boron amine complexes of borate esters, microencapsulated hydrazides, and modified imidazole adducts. The weight of the curing agent is 5 to 12 parts, and can be any value of 5 parts, 8 parts, and 12 parts, as long as it meets the range requirements of 5 to 12 parts (including the endpoint values of 5 parts and 12 parts). In this application, the curing agent plays a vital role in the high Tg single-component epoxy adhesive for locking motor coils. It is a catalyst that initiates the cross-linking reaction between epoxy resin molecules, and reacts chemically with the functional groups in the epoxy resin through its active groups to form a three-dimensional network structure, thereby transforming the adhesive from liquid to solid. The type and amount of the curing agent directly affect the curing speed, degree of curing and final performance of the adhesive.
[0058] Specifically, the weight proportion of the high toughness epoxy resin is 15 to 50 parts, and can be any value among 15 parts, 18 parts, 28 parts, 35 parts, and 50 parts, as long as it meets the range requirement of 15 to 50 parts (including the endpoint values of 15 parts and 50 parts).
[0059] High toughness epoxy resin, in terms of weight percentage, includes the following raw materials:
[0060] Low viscosity epoxy resin 67.5~90%
[0061] Isocyanate silane 9.4~30%
[0062] Catalyst 0.1~0.5%
[0063] Water reducing agent 0.5-2%;
[0064] At least one of the low-viscosity bisphenol A epoxy resin and the low-viscosity bisphenol F epoxy resin;
[0065] Specifically, low-viscosity epoxy resin, as the main component (67.5% to 90%) of high-toughness epoxy resin, mainly plays the role of providing matrix material. It has good fluidity and permeability, which can ensure that the high-toughness epoxy resin is evenly mixed during the preparation process and forms a tough and stable structure in the final product. The low viscosity property also helps to improve the adhesion and processing performance of the epoxy resin.
[0066] The isocyanate silane is at least one of 3-isocyanate propyl trimethoxy silane and 3-isocyanate propyl triethoxy silane.
[0067] Specifically, isocyanate silane (such as 3-isocyanate propyl trimethoxy silane, 3-isocyanate propyl triethoxy silane) is used as a crosslinking agent, and its isocyanate group reacts with the hydroxyl group or other active groups in the epoxy resin to form a crosslinked network structure. This crosslinked structure can significantly improve the mechanical properties, heat resistance and chemical resistance of the epoxy resin, thereby enhancing the toughness and durability of the high-toughness epoxy resin.
[0068] The catalyst is at least one of dibutyltin dilaurate, bismuth isooctanoate and bismuth neodecanoate.
[0069] Specifically, catalysts (such as dibutyltin dilaurate, bismuth isooctanoate, bismuth neodecanoate, etc.) play a role in accelerating chemical reactions in the preparation of high-toughness epoxy resins. They can reduce the activation energy of the reaction, promote the cross-linking reaction between resin molecules, and enable the reaction to achieve a higher conversion rate in a shorter time, thereby improving production efficiency and product quality.
[0070] The water reducing agent is a molecular sieve.
[0071] Specifically, the water reducer is mainly used in the high-toughness epoxy resin to remove moisture from the base resin, reduce the by-products produced by the reaction between the isocyanate group and water, and reduce the quality of the high-toughness epoxy resin, thereby improving the coil locking effect of the entire product.
[0072] The preparation method of the high-toughness epoxy resin comprises the following steps:
[0073] The material is taken according to the weight percentage of the raw material of the high-toughness epoxy resin; the low-viscosity epoxy resin, the catalyst and the water reducer are mixed and vacuumized; the temperature is lowered, and isocyanate silane is added to react; after the reaction is completed, the high-toughness epoxy resin is washed and dried to obtain the high-toughness epoxy resin.
[0074] Therefore, the high-toughness epoxy resin prepared by the above-mentioned raw material combination and preparation method can absorb and disperse energy when subjected to external forces through its cross-linking structure and toughening mechanism, thereby slowing down stress concentration and crack propagation. In addition, the synergistic effect of low-viscosity epoxy resin and components such as isocyanate silane further enhances the toughness and adhesion of the high-toughness epoxy resin. The high-toughness epoxy resin enables the adhesive to better adapt to the complex working environment of the motor coil, which plays a role in enhancing the toughness of the adhesive and improving impact resistance and durability.
[0075] Preparation Example 1
[0076] High toughness epoxy resin, in terms of weight percentage, includes the following raw materials:
[0077] 67.5% low viscosity epoxy resin, 30% isocyanate silane, 0.5% catalyst, and 2% water reducer.
[0078] The preparation method of high-toughness epoxy resin comprises the following steps:
[0079] ① EXA-830LVP low-viscosity bisphenol F epoxy resin: 67.5 parts, 3A molecular sieve: 2 parts, bismuth neodecanoate: 0.5 parts, are added into the reaction; heated to 110-120°C, vacuum degree ≤-95kPa, vacuum for 120 minutes; then the water content of the base glue is determined by Karl Fischer moisture tester to be ≤0.05%, and then proceed to the next step.
[0080] ② Cool the base rubber to 60-65°C, gradually add 30 parts of tri-isocyanatepropyltrimethoxysilane dropwise under nitrogen atmosphere, and then heat to 85-90°C and keep reacting for 120 minutes.
[0081] ③ After the reaction is completed, the temperature is lowered to room temperature to obtain a reactant; the reactant is washed with xylene and deionized water in sequence to remove unreacted substances; and finally, the reactant is dried to obtain a high-toughness epoxy resin.
[0082] Preparation Example 2
[0083] High toughness epoxy resin, in terms of weight percentage, includes the following raw materials:
[0084] Low viscosity epoxy resin 90%, isocyanate silane 9.4%, catalyst 0.1%, water reducing agent 0.5%.
[0085] The preparation method of high-toughness epoxy resin comprises the following steps:
[0086] ① EXA-830LVP low-viscosity bisphenol F epoxy resin: 90 parts, 3A molecular sieve: 0.5 parts, bismuth neodecanoate: 0.1 parts, are added into the reaction; heated to 110-120°C, vacuum degree ≤-95kPa, and vacuumed for 120 minutes; then the water content of the base glue is determined by a Karl Fischer moisture tester to be ≤0.05%, and then proceed to the next step.
[0087] ② Cool the base rubber to 60-65°C, gradually add 9.4 parts of tri-isocyanatepropyltrimethoxysilane dropwise under nitrogen atmosphere, and then heat to 85-90°C and keep the reaction for 120 minutes.
[0088] ③ After the reaction is completed, the temperature is lowered to room temperature to obtain a reactant; the reactant is washed with xylene and deionized water in sequence to remove unreacted substances; and finally, the reactant is dried to obtain a high-toughness epoxy resin.
[0089] Example 1
[0090] A high Tg one-component epoxy adhesive for locking a motor coil comprises the raw materials in Tables 1 and 2 below:
[0091] Table 1
[0092]
[0093]
[0094] Table 2
[0095]
[0096] The preparation method of the high Tg single-component epoxy adhesive for locking the motor coil comprises the following steps:
[0097] The raw materials in Table 1 were placed in a reaction vessel, mixed and stirred at a speed of 800-1000 RPM and a temperature of 50°C for 30 minutes; then the temperature was raised to 100°C, and the vacuum degree was ≤-95 kPa, and the mixture was stirred and evacuated for 60 minutes.
[0098] After the vacuuming is completed, the vacuum is opened, nitrogen is filled for protection, and the temperature is lowered to 50°C, and the raw materials (curing agent) in Table 2 are added;
[0099] Add appropriate amount of dry ice to lower the material temperature during stirring, stir and mix all materials evenly, vacuum for 30 minutes under the condition of vacuum degree: ≤-95kPa, then the epoxy adhesive can be obtained and stored in a sealed container at -15℃.
[0100] Comparative Example 1
[0101] A high Tg one-component epoxy adhesive for locking a motor coil, comprising the raw materials in Tables 3 and 4 below;
[0102] Table 3
[0103]
[0104]
[0105] Table 4
[0106]
[0107] The preparation method of the high Tg single-component epoxy adhesive for locking the motor coil comprises the following steps:
[0108] The raw materials in Table 3 were placed in a reaction vessel, and mixed and stirred at a speed of 800-1000 RPM and a temperature of 50°C for 30 minutes; then the temperature was raised to 100°C, and the vacuum degree was ≤-95 kPa, and the mixture was stirred and evacuated for 60 minutes.
[0109] After the vacuuming is completed, the vacuum is opened, nitrogen is filled for protection, and the temperature is lowered to 50°C, and the raw materials (curing agent) in Table 4 are added;
[0110] Add appropriate amount of dry ice to lower the material temperature during stirring, stir and mix all materials evenly, vacuum for 30 minutes under the condition of vacuum degree: ≤-95kPa, then the epoxy adhesive can be obtained and stored in a sealed container at -15℃.
[0111] Example 2
[0112] A high Tg one-component epoxy adhesive for locking a motor coil, comprising the raw materials in Table 5 below;
[0113] Table 5
[0114]
[0115]
[0116] The preparation method of the high Tg single-component epoxy adhesive for locking the motor coil, the specific process and parameter control are consistent with those in Example 1;
[0117] Example 3
[0118] A high Tg one-component epoxy adhesive for locking a motor coil, comprising the raw materials in Table 6 below;
[0119] Table 6
[0120]
[0121] The preparation method of the high Tg single-component epoxy adhesive for locking the motor coil, the specific process and parameter control are consistent with those in Example 1;
[0122] Example 4
[0123] A high Tg one-component epoxy adhesive for locking a motor coil, comprising the raw materials of Table 7 below;
[0124] The preparation method of the high Tg single-component epoxy adhesive for locking the motor coil is consistent with Example 1 in terms of specific process and parameter control.
[0125] Table 7
[0126]
[0127]
[0128] Performance test 1: The above-mentioned Example 1 and Comparative Example 1 were prepared according to the corresponding sample size requirements, and the conditions were: 85°C / 45min+110°C / 60min+130°C / 60min for curing, and the physical and chemical performance parameters thereof were measured and shown in Table 8 below;
[0129] The detection methods involved are:
[0130] ① Tg value: Use a 3.0±0.2mm thick solidified block to make the Tg value of the experimental block according to the TMA method of GB T 22567-2008 "Test method for glass transition temperature of electrical insulating materials";
[0131] ② Hardness: Use a 6.0±0.2mm thick cured block to measure the hardness value according to GB T 531.1-2008 “Test method for indentation hardness of vulcanized rubber or thermoplastic rubber”;
[0132] ③ Water absorption rate, using a specimen with a length and width of 61±1mm and a thickness of 1±0.1mm, according to the standard GB T1034-2008 "Water absorption rate test";
[0133] ④ Elastic modulus, dynamic mechanical analyzer (DMA) amplitude: 10μm, 25℃
[0134] Table 8
[0135] Tg value hardness Water absorption Elastic modulus Example 1 141.86℃ 92D 0.13% 6951MPa Comparative Example 1 115.50℃ 90D 0.15% 7190MPa Example 2 136.58℃ 92D 0.14% 7315MPa Example 3 142.36℃ 93D 0.12% 7589MPa Example 4 140.25℃ 92D 0.13% 7403MPa
[0136] Among them Figure 1-2 As shown, the Tg diagram was measured using a TA Instruments TMA450 thermomechanical analyzer at a temperature of 25°C to 220°C and a constant temperature rise rate of 5K / min.
[0137] like Figure 3-4 The figure shows the elastic modulus measured by using the DMA303 dynamic thermomechanical analyzer from NETZSCH, Germany, at a temperature of -40°C to 200°C and an amplitude of 10 μm.
[0138] It can be seen from Table 8 that, from the perspective of Tg value, the adhesive prepared in the embodiment is higher than the temperature of the hottest point in the winding insulation when the motor is running, which is 130°C for Class B materials, indicating that the adhesive fully meets the requirements as an insulating material; at the same time, from the analysis of the elastic modulus, the modulus at 25°C is only 6951MPa, indicating that the adhesive has a certain toughness, thereby ensuring that it will not fall off during the operation of the motor and ensuring the service life of the product.
[0139] Performance test 2: The performance change of the adhesive itself is characterized by testing the body strength and the change of the adhesive adhesion is characterized by testing the shear strength. The above-mentioned Example 1 and Comparative Example 1 are prepared according to the corresponding sample size requirements, and the conditions are: 85°C / 45min+110°C / 60min+130°C / 60min for curing, and then aging for 168h at a temperature of 85°C and a humidity of 85% and aging for 168h at -40°C to 125°C. The physical and chemical performance parameters are shown in Tables 9 and 10 below;
[0140] Table 9
[0141]
[0142] Table 10
[0143]
[0144] Note: The dimensions of the test specimens are as follows:
[0145] Body strength: GB / T 1040.2-2022 5A specimen; Shear strength: GB / T7124-2008 stainless steel lap size 25*12.5*0.2mm
[0146] The experimental conditions were carried out according to the following standards:
[0147] GB / T 2423.22-2012 Environmental testing Part 2: Test method Test N: Temperature change
[0148] GB / T 2423.40-2013 Environmental testing Part 2: Test method Experiment Cx: Unsaturated high pressure steam steady state wet heat
[0149] From Tables 9 and 10 and combined Figure 5-6 It can be seen that the bulk strength and shear strength of the adhesive of the present invention do not decay after aging, and even increase to a certain extent, while the comparative data show serious decay. This proves that the high-toughness epoxy resin described in this application can fully solve the problem of insufficient lifespan faced by current products.
[0150] The raw materials or reagents used in the examples and comparative examples of the present invention are all purchased from mainstream manufacturers in the market. Those without indicating the manufacturer or concentration are all analytically pure raw materials or reagents that can be routinely obtained. As long as they can play the expected role, there is no special limitation.
[0151] The instruments and equipment used in this embodiment are all purchased from major manufacturers in the market, and there is no particular limitation as long as they can play the expected role. In this embodiment, if no specific technology or conditions are specified, the technology or conditions described in the literature in this field or the product instructions are used. The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention can also be implemented in other ways. Any obvious replacement without departing from the concept of the present invention is within the protection scope of the present invention.
Claims
1. A high Tg one-component epoxy adhesive for locking motor coils, characterized in that: In parts by weight, the following raw materials are included: 5-25 parts of multifunctional epoxy resin, 15-50 parts of high-toughness epoxy resin, 0.1-0.5 parts of thixotropic agent, 0.5-1.5 parts of colorant, 0.1-0.5 parts of wetting and dispersing agent, 0.5-2 parts of defoaming agent, 15-40 parts of functional filler, 0.5-3 parts of antioxidant, 5-12 parts of curing agent; The high-toughness epoxy resin includes the following raw materials by weight percentage: Low viscosity epoxy resin 67.5~90% Isocyanate silane 9.4~30% Catalyst 0.1~0.5% Water reducing agent 0.5-2%; At least one of the low-viscosity bisphenol A epoxy resin and the low-viscosity bisphenol F epoxy resin; The isocyanate silane is at least one of 3-isocyanate propyl trimethoxy silane and 3-isocyanate propyl triethoxy silane.
2. The high Tg one-component epoxy adhesive for locking motor coils according to claim 1, characterized in that: The catalyst is at least one of dibutyltin dilaurate, bismuth isooctanoate and bismuth neodecanoate.
3. The high Tg one-component epoxy adhesive for locking motor coils according to claim 1, characterized in that: The water reducing agent is a molecular sieve.
4. The high Tg one-component epoxy adhesive for locking motor coils according to claim 1, characterized in that: The preparation method of the high-toughness epoxy resin comprises the following steps: The material is taken according to the weight percentage of the raw material of the high-toughness epoxy resin; the low-viscosity epoxy resin, the catalyst and the water reducer are mixed and vacuumized; the temperature is lowered, and isocyanate silane is added to react; after the reaction is completed, the high-toughness epoxy resin is washed and dried to obtain the high-toughness epoxy resin.
5. The high Tg one-component epoxy adhesive for locking motor coils according to claim 1, characterized in that: The multifunctional epoxy resin is at least one of 4,4'-diaminodiphenylmethane epoxy resin, 4-(diglycidylamino)phenyl glycidyl ether, sorbitol glycidyl ether, and phenol-type novolac epoxy resin.
6. The high Tg one-component epoxy adhesive for locking motor coils according to claim 1, characterized in that: The thixotropic agent is at least one of bentonite, fumed silica and polyethylene wax.
7. The high Tg one-component epoxy adhesive for locking motor coils according to claim 1, characterized in that: The functional filler is at least one of nano silicon dioxide, nano aluminum oxide and silicon dendrimer.
8. The high Tg one-component epoxy adhesive for locking motor coils according to claim 1, characterized in that: The antioxidant is at least one of a hindered amine antioxidant, a phosphite antioxidant, and a hindered phenol antioxidant.
9. The high Tg one-component epoxy adhesive for locking motor coils according to claim 1, characterized in that: The curing agent is at least one of microencapsulated dicyandiamide, boron amine complex of borate ester, microencapsulated hydrazide and modified imidazole adduct.
10. The method for preparing the high Tg one-component epoxy adhesive for locking motor coils according to any one of claims 1 to 9, characterized in that: The following steps are involved: Take materials according to the weight of the raw materials of the high Tg single-component epoxy adhesive for locking the motor coil; put multifunctional epoxy resin, high-toughness epoxy resin, thixotropic agent, colorant, wetting dispersant, defoamer, functional filler and antioxidant into a reaction container, mix them evenly, and then heat to 100° C. for vacuum treatment; The temperature is lowered to 40-60°C, a curing agent is added, and the mixture is mixed evenly under vacuum to obtain a high Tg single-component epoxy adhesive for locking the motor coil.
Citation Information
Patent Citations
High-toughness high-Tg-value epoxy resin and preparation method
CN104559064A
Cited By
Low-temperature fast-curing epoxy prepreg for battery cover and preparation method of low-temperature fast-curing epoxy prepreg
CN120647992A
